1991
DOI: 10.1095/biolreprod45.4.540
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Secretion by Oviductal Transport-Stage Equine Embryos1

Abstract: This study was conducted to identify embryonic products whose secretion was temporally associated with the oviductal transport period of the mare. Chemicals secreted by oviductal-transport-stage equine embryos were identified by incubating Day 6 or Day 7 early uterine embryos with 35S-methionine/cysteine, 3H-progesterone, or 3H-arachidonic acid for 24 h, and subsequently identifying radioactively labeled proteins (SDS-PAGE; n = 3 embryos), steroids (HPLC; n = 3 embryos), or prostaglandins (HPLC; n = 3 embryos)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 21 publications
3
55
0
3
Order By: Relevance
“…The release of prostaglandins by day 5-16 equine conceptuses incubated in vitro has been documented previously (Watson and Sertich, 1989;Weber et al, 1991aWeber et al, , 1992Vanderwall et al, 1993); in the present study the known period of PGE 2 and PGF 2α secretion was extended to day 32 of gestation. In addition, it was demonstrated that the cyclooxygenase inhibitor flunixin meglumine suppressed the release of PGE 2 by cultured day 14 blastocysts, thereby confirming that PGE 2 is synthesized de novo by the conceptus, at least at this stage of gestation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The release of prostaglandins by day 5-16 equine conceptuses incubated in vitro has been documented previously (Watson and Sertich, 1989;Weber et al, 1991aWeber et al, , 1992Vanderwall et al, 1993); in the present study the known period of PGE 2 and PGF 2α secretion was extended to day 32 of gestation. In addition, it was demonstrated that the cyclooxygenase inhibitor flunixin meglumine suppressed the release of PGE 2 by cultured day 14 blastocysts, thereby confirming that PGE 2 is synthesized de novo by the conceptus, at least at this stage of gestation.…”
Section: Discussionsupporting
confidence: 81%
“…failure of the cyclo-oxygenase inhibitor to reduce PGF 2α secretion markedly during the 1 h incubation indicates that a large proportion of the PGF 2α released during this time was pre-formed. In both cases, prostaglandins secreted by the early equine conceptus appear to derive primarily from the bilaminar omphalopleure, as the bilaminar choriovitellus was the major source of prostaglandins during days 28-32, as it is in day 20-24 sheep conceptuses (Lewis and Waterman, 1985), and because equine conceptuses secrete prostaglandins from as early as day 5 after ovulation (Weber et al, 1991a). In this context, it is not surprising that PGE 2 and PGF 2α were present at higher concentrations in yolk sac than allantoic fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with oviductal transport [Weber et al, 1991a;1992a]; and 3) intraoviductal PGE 2 treatment of bred mares has been found to hasten oviductal transport [Weber et al, 1991b].…”
Section: Introductionmentioning
confidence: 98%
“…The oviductal transport-stage equine embryo appears to initiate its selective oviductal transport [Freeman et al, 1992]. Prostaglandin E 2 (PGE 2 ) secreted by equine embryos has been proposed to initiate oviductal transport in mares because 1) PGE 2 is a major secretory product of oviductal transport-stage embryos [Weber et al, 1991a]; 2) embryonal secretion and oviductal specific binding of PGE 2 are temporally associated 1 This work was funded by the Idaho Equine Education Bill, and it is part of the Idaho Experiment Station Series No. 94A14.…”
Section: Introductionmentioning
confidence: 99%